Pengaruh Visitor Attraction, Kualitas Produk, Harga Dan Lokasi Terhadap Keputusan Pembelian Di Societe Cafe Kediri - Diah Ayu Kusuma Wardani (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2023)
The issues discussed are product quality, price and promotion to reflect the relationship to product purchasing decisions at Societe Café Kediri. The population and samples taken were product-loving consumers who had purchased products at Societe Cafe Kediri. The analysis technique used is Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis and Hypothesis Testing. The research results show that product quality, price and promotion simultaneously have a significant influence on car purchasing decisions, this can be seen from the results of the F test, the F sig value is 0.000 < 0.05. The determinant coefficient value (R2) is 0.839. This can be interpreted that the independent variables (product quality, price and promotion) can explain the dependent variable (purchase decision) by 83.9%, while the rest is explained by other factors that were not studied such as purchasing service factors, service delivery, location and others. -other.